Thermal–electrical–hydraulic properties of Al2O3–SiO2 hybrid nanofluids for advanced PEM fuel cell thermal management - Khalid, Saifuddin; Zakaria, Irnie; W. H., Azmi; Mohamed, W. A. N. W. (Springer, 2021)
Hybrid nanofluid is a new revolutionized cooling liquid with improved thermo-physical properties as compared to conventional coolant. This paper presents the feasibility of hybrid Al2O3–SiO2 nanofluids as an advanced coolant for PEM fuel cell application in terms of thermal–electrical–hydraulic thermo-physical properties. Nine mixture ratios of Al2O3–SiO2 were used in this experiment, ranging from 10:90 to 90:10 mixture ratios. The result demonstrated that both thermal conductivity and electrical conductivity decreased as the percentage of Al2O3 was increased in the mixture. In contrast, the dynamic viscosity property increased as the Al2O3 percentage ratio was increased. In summary, property enhancement ratio (PER) of thermo-hydraulic (PERt/v) and thermo-electrical (PERt/e) was established. Both PERt/v and PERt/e analyses favor 10:90 ratio of Al2O3–SiO2 hybrid as the most feasible ratio for the implementation in PEMFC. This is due to the dominant effect of thermal over viscosity and electrical conductivity.